Pengaruh Motivasi Kerja, Disiplin Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan di PT Kalimutu Mitra Perkasa - Muhammad Syamsul Hidayat; Didin Hikmah Perkasa; Muhamad Al Faruq Abdullah; Wenny Desty Febrian; Yanthy Herawaty Purnama; Leli Deswindi; Muhamad Ekhsan (Journal of Management and Bussines (JOMB), 2024)
This research aims to investigate the influence of Leadership Style, Motivation and Work Discipline on Employee Performance at PT Kalimutu Mitra Perkasa. Data was collected through a questionnaire using the Likert scale method, and data analysis was carried out using Structural Data Analysis, specifically the Partial Least Square Equation Model. Evaluation was carried out on the measurement model (Outer Model) and structural tests (Inner Model) using the SEM PLS data processing tool. The research results show that work motivation has a positive influence on employee performance with an original sample value of 0.438, and a t-statistic value > t-table (2.767 > 1.96), indicating that work motivation has a significant effect on performance. Work Discipline has also been proven to have a positive effect on employee performance with an original sample value of 0.358, and a t-statistic value > t-table (2.262 > 1.96), indicating that Work Discipline has a significant impact on employee performance. However, Leadership Style was not proven to have a significant influence on Employee Performance, with an original sample value of 0.106, and a t-statistic value < t-table (0.872 < 1.96). Conclusion, that Leadership Style does not have a significant influence on employee performance at PT Kalimutu Mitra Perkasa. In conclusion, this research contributes to understanding the factors that influence employee performance in these organizations, and can be a basis for developing more effective human resource management strategies. Keywords: Work discipline, Leadership Style, Employee Performance, Motivation